Li and U Isotopes as a Potential Tool for Monitoring Active Layer Deepening in Permafrost Dominated Catchments - Hindshaw, Ruth S.; Aciego, Sarah M.; Tipper, Edward T. (Frontiers in Earth Science, 2018)
Permafrost in the Arctic is decreasing in extent and the depth of the seasonally thawed layer, the active layer, is increasing. Increased exposure to water is increasing fluxes of organic and inorganic solutes with potential impacts for the global carbon cycle and downstream ecosystems. Understanding the relationship between solute release and active layer depth will be critical for modeling environmental impact, especially in inaccessible regions where there is a lack of data. In this study, we focus on the potential for the isotopes of lithium (Li) and uranium (U) to track active layer extent in two permafrost-dominated catchments in Svalbard: one glaciated and one unglaciated. These isotope systems can be measured to a much higher precision than concentration measurements and act as sensitive tracers of environmental change. The extent of Li isotope fractionation provides information on the balance between dissolution of primary phases and formation of secondary phases, such as clay minerals and oxides. The U activity ratio provides information on water-rock interaction times and physical properties. We observe contrasting behavior between the two catchments. The highest U activity ratios and Li isotope values (those most distinct from bedrock) are observed in summer in the unglaciated catchment, when the active layer depth is expected to be at its maximum extent, whereas negligible seasonal variation and the lowest values are observed in the glaciated catchment. We therefore propose that the extent of solute acquisition is directly linked to the active layer depth, which is restricted in the glaciated catchment due to a layer of “dead ice” underneath the glacial outwash plain, and could therefore provide a valuable tool to assess changes in active layer depth at catchment scales.